Computational study of air ventilation in high tension electrical cable tunnel / Sarveswaran Subramaniam - Sarveswaran, Subramaniam (2018)
The chive concern in this project is the study and develop a ventilation system for a High Tension Electrical Cable Tunnel. This is because the cables in the tunnels generates heat up to about 600C. These cables are laid in a trefoil configuration with 6 circuits running in an 80-metre-long with 3 metre diameter tunnel. To analyse the effects of air velocity and air flow on the surrounding of the interior of the tunnel a model of the tunnel was created using Solid works, CAD software. The parameters of the analysis were the Velocity and air flow which was determined from Air Change Per-Hour (“AC/Hr”). Using the assumption of Air Change Per-Hour with the volume of the tunnel designed, the velocities and air flow in tunnel were determined. the velocities obtained were used in the ANSYS Computational Fluid Dynamics software to determine the temperature at the mid of the tunnel at various ambient temperature and velocities to determine the best velocity and air flow for the tunnel ventilation system. The main emphasis was given for the ambient temperature of 330C which the average temperature of the area is where the tunnel is proposed to be built. All the results are presented in the Conclusion and Recommendation in this report.